Directive Illocutionary Acts Used by The Characters in You People Movie - I Gusti Agung Ayu Aries Sita; Ni Wayan Suastini (RETORIKA: Jurnal Ilmu Bahasa, 2026)
Illocutionary acts refer to the speaker’s intention in producing utterances, particularly in directing others to perform certain actions. This study analyzes the types of directive illocutionary acts found in You People movie using Yule’s (1996) theory. The research aims to identify and classify the directive illocutionary acts produced by the characters in the movie. A qualitative descriptive method was applied in analyzing the data. The findings reveal four types of directive illocutionary acts, namely ordering, forbidding, requesting, and suggesting. The results show that requesting appears most frequently with 16 data, followed by ordering (15 data), suggesting (8 data), and forbidding (5 data). These findings indicate that directive illocutionary acts are essential in expressing intentions and influencing others in social interactions within the movie.